The Influence of IoT Simulation in the Learning Process: A Case Study - Bayani, Majid (2020)
Internet of things (IoT) is a relatively novel technology which provides connection between things. It was presented for the first time by Kevin Ashton in 90´s.The software and hardware development of IoT is not growing as the same rates as the implementations of its applications in the human life such as: education, administration, business, health, security and our social life. Education is one the most popular field which IoT is presented. This research is a concise survey of a real case which studies influence of the IoT in the learning process. A theoretical revision along with a statistical analysis of a real case is discussed in this work. Finally, the results revealed several attractive impacts of the IoT simulation in the learning process which be outlined in details along the paper.